Holy foolery in the life of Japan a historical overview - Higuchi, Kazunori 1959-; Miller, Waku; LTCB International Library Trust; Kokusai Bunka Kaikan (Tokyo, Japan) (Tokyo International House of Japan, 2015)
"On the following pages, we will retrace the origins and evolution of holy foolery in Japan. We will witness its near extinguishment through the process of modernization and globalization. We will see why Japan needs holy foolery more than ever. And we will identify contemporary traces that suggest a basis for optimism about laughter's possible resurgence"--From jacket.
The Origins of Laughter -- The Gods, Laughter, and the Japanese -- Divine Mysteries -- Laughter amid the Evolution of Communities -- Urbanization and Modernization -- Globalization -- Eminent Interpreters of Foolery -- Natural Disasters and Transcendent Laughter
At head of title: LTCB International Library Trust/International House of Japan.
"This book originally appeared in Japanese as Warai no Nihon bunka - Oko-no-mono wa doko e kieta no ka? (Tokyo: Tokai Education Research Institute, 2013)"--Title page verso.
Includes index.
In English
Keywords: Laughter -- Japan -- History; Laughter in literature; Japan -- Civilization; Japan